The Relationship Between Fasting Blood Glucose and the Severity of Diabetic Retinopathy : A Comprehensive Systematic Review - Ramadhani Ferrial Nugraha; Djonny Djuarsa; Gaby Syafira Siti Halimatussa'diah (International Medical Journal Corp. Ltd, 2026)
Introduction: Diabetic retinopathy (DR) is a leading cause of blindness. While glycated hemoglobin (HbA1c) is the standard glycemic metric, the role of fasting blood glucose (FBG) as an independent predictor of DR severity remains debated. This systematic review synthesizes evidence on the relationship between FBG and DR severity. Methods: A systematic review of 80 studies (cross-sectional, cohort, RCTs, et al) was conducted. Data were extracted on FBG measurement, DR severity classification, study populations, confounding variables, and the direct association between FBG and DR. Results: A positive association between elevated FBG and DR presence/severity was found across diverse populations. Meta-analyses reported pooled odds ratios (OR) for DR per unit FBG increase ranging from 1.19 (95% CI: 1.13-1.26) to 2.41 (95% CI: 1.63-3.57) when combined with HbA1c. Longitudinal studies identified FBG thresholds (e.g., 6.9-7.4 mmol/L) for predicting DR risk. Large RCTs (ACCORD, DCCT) confirmed that intensive glycemic control, which reduces FBG, significantly slows DR progression. Fasting glucose variability emerged as an independent risk factor for DR in type 2 diabetes, even after adjusting for HbA1c. However, several studies found FBG lost independent significance when HbA1c was included in multivariable models. Key confounders included diabetes duration, hypertension, and renal function. Discussion: The relationship between FBG and DR is significant but complex. The evidence supports FBG as a robust risk marker, particularly in type 2 diabetes, with a dose-response relationship and the added risk of glycemic variability. However, HbA1c remains a superior predictor of cumulative glycemic exposure. Discrepancies across studies may be explained by differences in diabetes type, study design (cross-sectional vs. longitudinal), and whether analyses adjusted for HbA1c. The effect of FBG is most pronounced in settings where HbA1c is unavailable or as a component of overall glycemic control. Conclusion: Elevated FBG and its variability are significant, independent risk factors for DR presence and severity, especially in type 2 diabetes. While HbA1c remains a crucial metric, FBG provides valuable prognostic information. Clinical management should focus on achieving recommended FBG targets and minimizing glycemic variability to reduce DR risk.